2019
DOI: 10.1097/pas.0000000000001352
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement in Vascular Invasion Scoring and the Added Value of Immunohistochemistry for Vascular Markers to Predict Disease Relapse in Stage I Testicular Nonseminomas

Abstract: Vascular invasion has been identified as an informative risk factor for relapse in stage I testicular nonseminomas, used to tailor treatment. We investigated interobserver agreement in vascular invasion reporting and studied the potential additional value of immunohistochemistry for vascular markers for predicting relapse. Patients (n = 52) with stage I testicular nonseminomas undergoing surveillance (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) were included (median foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Vascular invasion is the most discriminative biomarker so far, even in multivariable analyses [12,13]. Recently, we confirmed the value of vascular invasion assessment in a surveillance cohort of stage I non-seminoma patients [16]. Moreover, we demonstrated that all patients depicting simultaneously lymph vessel and blood vessel invasion developed relapse; possibly, if validated, this should further identify high-risk patients.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Vascular invasion is the most discriminative biomarker so far, even in multivariable analyses [12,13]. Recently, we confirmed the value of vascular invasion assessment in a surveillance cohort of stage I non-seminoma patients [16]. Moreover, we demonstrated that all patients depicting simultaneously lymph vessel and blood vessel invasion developed relapse; possibly, if validated, this should further identify high-risk patients.…”
Section: Introductionsupporting
confidence: 64%
“…One of the limitations of our work is its retrospective nature and the relative small cohort size. However, the power is the true surveillance cohort of 70 stage I patients (partly already described in [16]), avoiding confounding factors related to any treatment except initial orchiectomy. Also, and because our cases derive from several institutions across the Netherlands, our findings do not reflect a selection bias due to inclusion of patients from a single center.…”
Section: Discussionmentioning
confidence: 99%
“…In seminomas, only the size of the primary tumor has been validated, although this is not clinically useful as the difference between high-and low-risk relapse estimates range from 5-10% to 20-25% [5,6]. For NSGCTs, the presence of lymphovascular invasion (LVI) and, to a lesser extent, the predominance of embryonal carcinoma are associated with relapse [7][8][9][10]. The presence of LVI confers a 50% chance of relapse compared with 15% in those without, while pooled relapse rates were 40% for patients with embryonal carcinoma predominance.…”
Section: Introductionmentioning
confidence: 99%
“…The latter comprise a complex array of subtypes that include embryonal carcinoma (EC), choriocarcinoma (CH), yolk sac tumor (YST), and teratoma (TE) [1][2][3][4][5][6][7]. Overall, TGCTs represent a model of curable disease, with most patients presenting with stage I disease (around 70%), but approximately 75% of these are cured with orchiectomy alone, without the need for subsequent adjuvant treatments [4,8,9]. For those who require systemic therapy, TGCTs present extreme sensitivity to cisplatin-based chemotherapy, due to their unique molecular background [3,10].…”
Section: Introductionmentioning
confidence: 99%